Librarian Creativity to Improve Library Services and Librarian Performance - Adiatama, Pindyana (Record and Library Journal, 2021)
Background of the study: The college library is the heart of higher education. In the era of information technology today the needs and desires of the settlers vary and change. Librarians are required to be creative and have competence when managing libraries and serving the users. Librarians must develop better performance by paying attention to the quality of service to users. Purpose: The research aims to determine creativity to improve the service and performance of the librarian. Method: This research uses qualitative method. Findings: The results of this research are the efforts of the librarian in increasing the creativity of the librarian's performance, which can be seen from the skills and abilities gained by the librarians through a formal education of the libraries D3, S1 and S2. In addition to increasing the knowledge and insight of librarians write scientific works. Librarians also participate in and hold training, workshops, socialization and book reviews. Conclusion: The organizational environment encourages creativity such as awards given to librarians that can be seen in the performance and aspects of librarian behavior used to calculate incentives. In addition, the support of the leadership and the good team work also affects the creativity of the librarians.